Assessing the impacts of alcohol policies A microsimulation approach - Cecchini, Michele (OECD Health Working Papers, 2015)
Alcohol policies have significant potential to curb alcohol-related harms, improve health, increase productivity, reduce crime and violence, and cut government expenditure. The WHO Global Strategy to reduce the harmful use of alcohol provides a menu of policy options based on international consensus, which the OECD has used as a starting point in identifying a set of policies to be assessed in an economic analysis based on a computer simulation approach. This working paper provides a comprehensive illustration of the modelling approach, input data and underlying assumptions that have been used to carry out the analyses. The policies assessed in three country settings - Canada, the Czech Republic and Germany - include price policies, regulation and enforcement policies, education programmes and health care interventions. The results of the OECD analyses show that brief interventions in primary care, typically targeting high-risk drinkers, and tax increases, which affect all drinkers, have the potential to generate large health gains. The impacts of regulation and enforcement policies as well as other health care interventions are more dependent on the setting and mode of implementation, while school-based programmes show less promise. Alcohol policies have the potential to prevent alcohol-related disabilities and injuries in hundreds of thousands of working-age people in the countries examined, with major potential gains in their productivity. Most alcohol policies are estimated to cut health care expenditures to the extent that their implementation costs would be more than offset. Health care interventions and enforcement of drinking-and-driving restrictions are more expensive policies, but they still have very favourable cost-effectiveness profiles